Patients’ Knowledge and Habits Regarding Diabetic Foot Prevention Measures: Polyclinic of a Private University, Asunción, Paraguay, 2024 - Marcet Franco, Igor Ernesto; Cáceres Bogado , Clara Margarita; Giménez Reyes, María Belén; Maidana Pont, Ema Soledad; Barrios, Jazmín; Ríos Mujica , Patricia (Medicina Clínica y Social, 2025)
Introduction: Diabetes mellitus is a metabolic disorder associated with severe complications, including diabetic foot, a frequent cause of disability, hospitalization, and amputations. Despite the key role of healthcare personnel in patient education, knowledge and prevention gaps persist. Objective: To determine patients’ knowledge and habits regarding diabetic foot prevention measures at the Polyclinic of a Private University in Asunción, Paraguay, in 2024. Methodology: An observational, descriptive, and cross-sectional study was conducted among adult diabetic patients attending the Polyclinic. All consenting patients were included, while those with communication difficulties were excluded. A structured questionnaire was applied, and data were analyzed using descriptive statistics. Adequate knowledge or habits were defined as more than 50% of positive responses. Results: A total of 131 patients were included, predominantly male (70%), aged between 19 and 60 years. Overall, 64% demonstrated global knowledge of preventive measures. High awareness was observed regarding systemic complications of diabetes and the importance of specialized consultation, but lower knowledge was found concerning proper nail trimming and immediate action in case of injuries. Regarding habits, 79% of patients reported adequate preventive practices. Conclusion: Most patients showed favorable knowledge and habits for diabetic foot prevention, although specific areas for improvement were identified. These findings highlight the importance of continuous and targeted educational interventions to strengthen self-care practices.